Production of rare ginsenosides by biotransformation of Panax notoginseng saponins using Aspergillus fumigatus - Lian Yang; Dongmei Lin; Feixing Li; Xiuming Cui; Dengji Lou; Xiaoyan Yang (Bioresources and Bioprocessing, 2024)
Abstract Panax notoginseng saponins (PNS) are the main active components of Panax notoginseng. But after oral administration, they need to be converted into rare ginsenosides by human gut microbiota and gastric juice before they can be readily absorbed into the bloodstream and exert their effects. The sources of rare ginsenosides are extremely limited in P. notoginseng and other medical plants, which hinders their application in functional foods and drugs. Therefore, the production of rare ginsenosides by the transformation of PNS using Aspergillus fumigatus was studied in this research. During 50 days at 25 ℃ and 150 rpm, A. fumigatus transformed PNS to 14 products (1–14). They were isolated by varied chromatographic methods, such as silica gel column chromatography, Rp-C18 reversed phase column chromatography, semi-preparative HPLC, Sephadex LH-20 gel column chromatography, and elucidated on the basis of their 1H-NMR, 13C-NMR and ESIMS spectroscopic data. Then, the transformed products (1–14) were isolated and identified as Rk3, Rh4, 20 (R)-Rh1, 20 (S)-Protopanaxatriol, C-K, 20 (R)-Rg3, 20 (S)-Rg3, 20 (S)-Rg2, 20 (R)-R2, Rk1, Rg5, 20 (S)-R2, 20 (R)-Rg2, and 20 (S)-I, respectively. In addition, all transformed products (1–14) were tested for their antimicrobial activity. Among them, compounds 5 (C-K) and 7 [20 (S)-Rg3] showed moderate antimicrobial activities against Staphylococcus aureus and Candida albicans with MIC values of 6.25, 1.25 μg/mL and 1.25, 25 μg/mL, respectively. This study lays the foundation for production of rare ginsenosides. Graphical abstract